2004
DOI: 10.1111/j.1351-0754.2004.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of andic properties in soils from Galicia (NW Spain) under forest and agricultural use

Abstract: Summary The organic matter (OM) of soils with andic properties has long been considered highly stable because of the presence of Al–humus complexes and sorption of organic ligands onto amorphous compounds. In this study, we characterized soils under different land use regimes located within an amphibolitic massif close to Santiago de Compostela (Spain), where soils with andic properties are present. Slash and burn agriculture was a common practice in the area until the second half of the 20th century. Thereaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
(19 reference statements)
3
19
0
Order By: Relevance
“…(Takahashi et al, 2006a), as was later verified in a laboratory incubation (Miyazawa et al, 2013). These results are consistent with field studies that demonstrated a marked decrease in Al p and SOM contents of Ap horizons in Andosols following cultivation and liming (Saigusa et al, 1988;Verde et al, 2005).…”
Section: Organic Carbon Accumulation In Andosolssupporting
confidence: 87%
“…(Takahashi et al, 2006a), as was later verified in a laboratory incubation (Miyazawa et al, 2013). These results are consistent with field studies that demonstrated a marked decrease in Al p and SOM contents of Ap horizons in Andosols following cultivation and liming (Saigusa et al, 1988;Verde et al, 2005).…”
Section: Organic Carbon Accumulation In Andosolssupporting
confidence: 87%
“…This leads to the formation of stable organo-mineral complexes and to the sorption of organic ligands onto these amorphous compounds increasing the stability and accumulation of SOC. The formation of mineral-associated SOC complexes by aluminosiallitisation is an important geochemical mechanism for the stabilization of organic matter in soils developed on granites and quartz-rich metamorphic rocks (gneiss, schist and slate) and on soils with andic properties derived from mafic rocks (Macías et al, 1978;García-Rodeja et al, 1987Verde et al, 2005). The negative correlation coefficients observed in the remaining geologic classes is probably derived to their lower abundance of weatherable minerals and thus a lower supply of reactive metal forms which stabilize soil organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…For peat soils, we used the mean bulk density value reported in previous studies for peatlands of the studied area (Pontevedra-Pombal et al, 2004). The resulting map of BD was validated using an external dataset of BD measurements in epipedons of 62 soils from NW Spain obtained from references (Álvarez-Olleros, 2001;Brañas et al, 2000;García-Rodeja et al, 1987;Garea, 1983;Veiga et al, 2001;Verde et al, 2005). The validation of the BD map shows a high correlation between BD and organic matter content (R-squared = 0.79; RMSE = 0.16, MAE = 0.13, ME = 0.07), which indicates that BD is highly influenced by the organic matter content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations